2020
DOI: 10.1016/j.jmaa.2019.123731
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative boundedness of Littlewood–Paley functions on weighted Lebesgue spaces in the Schrödinger setting

Abstract: Let L := −∆ + V be the Schrödinger operator on R n with n ≥ 3, where V is a nonnegative potential which belongs to certain reverse Hölder class RH q (R n ) with q ∈

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…We point out that the quantitative weighted boundedness of Littlewood-Paley functions generated by fe −tL α g t>0 is not a simple analogue of [19] which deals with the case α = 1. For α = 1, it is well known that the heat kernel K t ð•Þ of the Laplace operator has a good decay properties.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…We point out that the quantitative weighted boundedness of Littlewood-Paley functions generated by fe −tL α g t>0 is not a simple analogue of [19] which deals with the case α = 1. For α = 1, it is well known that the heat kernel K t ð•Þ of the Laplace operator has a good decay properties.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, the quantitative weighted bounds for operators in the Schrödinger settings have been investigated by many researchers. Li et al [18] established the quantitative weighted boundedness of maximal functions, maximal heat semigroups, and fractional integral operators related to L. In 2020, Zhang and Yang [19] showed that the quantitative weighted boundedness for Littlewood-Paley functions in the Schrödinger setting. Bui et al [20] investigated the quantitative boundedness for square functions with new class of weights.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Yan et al [49] continued the above line of research and established the intrinsic square function characterizations of the Hardy type space H X (R n ) related to a ball quasi-Banach function space X satisfying some mild additional assumptions. For more applications of such intrinsic square functions, we refer the reader to [10,11,23,37,39,52].…”
Section: Introductionmentioning
confidence: 99%